2015
DOI: 10.14260/jemds/2015/2038
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy and Retrorenal Colon: Its Incidence and Complications

Abstract: OBJECTIVE:The aim of this study was to investigate retrorenal colon incidence in percutaneous nephrolithotomy (PCNL) and to discuss the necessity of routine preoperative CT and perform a cost analysis of this procedure. MATERIALS AND METHODS: Clinical data of 608 PCNL patients over a 5 year period (2008)(2009)(2010)(2011)(2012)(2013), was surveyed. The patient files were reviewed retrospectively, and only those who had abdominal computed tomography (CT) images before PCNL intervention were included in the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Colonic perforation complicates 0.3% of PCNL procedures [13]. A series by Reddy and Shaik also demonstrated that although rare, only two cases of colonic perforations occurred in patients where preoperative CT scans were not done [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colonic perforation complicates 0.3% of PCNL procedures [13]. A series by Reddy and Shaik also demonstrated that although rare, only two cases of colonic perforations occurred in patients where preoperative CT scans were not done [14].…”
Section: Discussionmentioning
confidence: 99%
“…Colonic injury with percutaneous renal access can result in sepsis, peritonitis, abscess formation, or fistula formation [14]. Early detection and conservative or endoscopic management with a course of antibiotics has been reported to have good success rates.…”
Section: Discussionmentioning
confidence: 99%